Case Report: Preimplantation Genetic Testing for X-Linked Severe Combined Immune Deficiency Caused by IL2RG Gene Variant - Ren, Jun; Peng, Cuiting; Zhou, Fan; Li, Yutong; Keqie, Yuezhi; Chen, Han; Zhu, Hongmei; Chen, Xinlian; Liu, Shanling (Frontiers in Genetics, 2022)
Preimplantation genetic testing (PGT) has been increasingly used to prevent rare inherited diseases. In this study, we report a case where PGT was used to prevent the transmission of disease-caused variant in a SCID-X1 (OMIM:300400) family. SCID-X1 is an X-linked recessive inherited disease whose major clinical manifestation of immune deficiency is the significant reduction in the number of T-cells and natural killer cells. This family gave birth to a boy who was a hemizygous proband whose IL2RG gene was mutated (c.315T＞A, p.(Tyr105*), NM_000206.3, CM962677). In this case, Sanger sequencing for mutated allele and linkage analysis based on single-nucleotide polymorphism (SNP) haplotype via next-generation sequencing were performed simultaneously. After PGT for monogenic disorder, we detected the aneuploidy and copy number variation (CNV) for normal and female carrier embryos. Four embryos (E02, E09, E10, and E11) were confirmed without CNVs and inherited variants at the IL2RG gene. Embryo E02 (ranking 4BB) has been transferred after considering the embryo growth rate, morphology, and PGT results. Prenatal genetic diagnosis was used to detect amniotic fluid cells, showing that this fetus did not carry the variant of the IL2RG gene (c.315T＞A). Ultimately, a healthy gilr who had not carried disease-causing variants of SCID-X1 confirmed by prenatal diagnosis was born, further verifying our successful application of PGT in preventing mutated allele transmission for this SCID family.